2007
DOI: 10.1093/brain/awm242
|View full text |Cite
|
Sign up to set email alerts
|

Recessive Twinkle mutations in early onset encephalopathy with mtDNA depletion

Abstract: Twinkle is a mitochondrial replicative helicase, the mutations of which have been associated with autosomal dominant progressive external ophthalmoplegia (adPEO), and recessively inherited infantile onset spinocerebellar ataxia (IOSCA). We report here a new phenotype in two siblings with compound heterozygous Twinkle mutations (A318T and Y508C), characterized by severe early onset encephalopathy and signs of liver involvement. The clinical manifestations included hypotonia, athetosis, sensory neuropathy, ataxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
141
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(146 citation statements)
references
References 28 publications
4
141
0
1
Order By: Relevance
“…These investigators further demonstrated that recombinant Y508C p72 hexamers have near WT DNA helicase activity with a slight reduction in single-stranded DNA binding affinity (43), results that corroborate the current work. The A318T substitution is only found as a compound heterozygous mutation with Y508C in a severe early onset encephalopathy with liver involvement and depletion of mtDNA in the liver (44,47). These observations that one A318T-, T457I-, or Y508C-substituted copy of C10orf2 is insufficient to induce disease strongly suggests that the remaining WT allele is sufficient for health or is able to rescue any biochemical deficiencies of the protein derived from the mutant allele.…”
Section: Discussionmentioning
confidence: 98%
“…These investigators further demonstrated that recombinant Y508C p72 hexamers have near WT DNA helicase activity with a slight reduction in single-stranded DNA binding affinity (43), results that corroborate the current work. The A318T substitution is only found as a compound heterozygous mutation with Y508C in a severe early onset encephalopathy with liver involvement and depletion of mtDNA in the liver (44,47). These observations that one A318T-, T457I-, or Y508C-substituted copy of C10orf2 is insufficient to induce disease strongly suggests that the remaining WT allele is sufficient for health or is able to rescue any biochemical deficiencies of the protein derived from the mutant allele.…”
Section: Discussionmentioning
confidence: 98%
“…Hakonen et al described a more severe disease associated with compound heterozygous Twinkle mutations in two brothers, who had very early-onset encephalopathy at around 6 months of age with abnormal eye, face, and limb movements, sensory neuropathy, and hypotonia (Hakonen et al 2007). The evolution was marked by the emergence of intractable epilepsy and liver failure, mimicking Alpers syndrome described in patients with POLG mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of the disease is between 1 and 2 years of age (Koskinen et al 1994). Recently, case studies of two children with early-onset encephalopathy and liver failure associated with Twinkle mutations were reported (Hakonen et al 2007). The phenotype was close to Alpers hepatocerebral syndrome (Alpers 1931), which is caused by mutations in POLG.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in C10orf2 have been associated with variable phenotypes, including infantile-onset spinocerebellar ataxia [11,[93][94][95][96][97], autosomal dominant PEO [98][99][100], and hepatocerebral MDS [101,102]. Mutations in C10orf2 are a rare cause of early-onset hepatocerebral MDS that has been reported in 5 children from 2 unrelated families.…”
Section: C10orf2-related Hepatocerebral Mdsmentioning
confidence: 99%